High-efficiency solar thermophotovoltaic system using a nanostructure-based selective emitter - Bhatt, Rajendra; Kravchenko, Ivan; Gupta, Mool (Solar energy, 2020)
•A high-efficiency STPV system was designed and fabricated.•Used a multilayer metal-dielectric coated selective emitter for spectral control.•Quantified optical and thermal losses at various stages of energy conversion.•Overall power conversion efficiency of 8.4% was recorded at 1676 K. In this work, we present the design, fabrication, optimization, and experimental results of a high-efficiency planar solar thermophotovoltaic (STPV) system utilizing a micro-textured absorber and a nanostructure multilayer metal-dielectric coated selective emitter fabricated on a tungsten (W) substrate. Light absorptance of more than 90% was achieved at visible and near-infrared wavelengths using the microtextured absorbing surface. The nanostructure selective emitter consists of two thin-film optical coatings of silicon nitride (Si3N4) and a layer of W in between to increase the surface emissivity in spectral regimes matching the quantum efficiency of the thermophotovoltaic (TPV) cells. Gallium antimonide (GaSb)-based TPV cells are used in our STPV design. The experiment was conducted at different operating temperatures using a high-power continuous wave laser diode stack as a simulated source of concentrated incident radiation. Our experimental setup measured a maximum electrical output power density of 1.71 W/cm2 at 1676 K STPV temperature, and the overall power conversion efficiency of 8.4% after normalizing the output power density to the emitter area. This is the highest STPV system efficiency reported so far for any experimental STPV device. The incident optical laser power on the absorber side was 131 W. This is equivalent to a solar concentration factor of ~2100, which is within the practical limit and readily achievable with Fresnel lens setup.